Era uma vez Frozen : o conto de fadas e suas ressignificações na circulação midiática - Haslinger, Evelin de Oliveira (Universidade do Vale do Rio dos Sinos, 2018)
This research is a study about the transformations of fairy tales in the society in process of mediatization. Our central objective is to investigate these changes from the movement of fairy tales, referring to their historical course. It means the flow of fairy tales, their updates and stays inscribed in circuits, namely in the flow forward (BRAGA, 2012) through multi-devices that reiterate the valorization and organize new forms of contact, modifying the public itself and its role. To that end, we selected a fairy tale for the formation of our survey, being: the animation "Frozen: a freezing adventure" (Disney, 2013). This piece of work stands out as one of the most popular fairy tales nowadays and is among the ones that generate the most media and non-media products. The research problem guiding our study is: How the meanings about Frozen built from the tension among grammars of production and recognition? Highlithing this problem, we return to the analysis of Frozen animation based on three instances: from book to animation; on animation and its circulation and, finally, the inscription of the fairy tale in a logic of consumption. As theoretical contributions we mobilize in particular the concepts of media society, mediatization and circulation with attention to Latin American authors. The work gives clues not only of changes in the media (from the printed to the digital book), but also in the very meaning of the story, which is increasingly co-managed by the social actors.
Keywords: Frozen; Midiatização; Contos de fadas; Circulação; Frozen; Midiatization; Fairy tale; Circulation; ACCNPQ::Ciências Sociais Aplicadas::Comunicação